Chemical recycling of refrigerator plastic waste by pyrolysis: Yields, product composition, and potential applications - Jonas Vogt; Axel D. Renno; Margret Fuchs; Tim Kurtz; Niklas Netsch; Frank Richter; Grazyna Straczewski; Britta Bergfeldt; Yuleika Carolina Madriz-Diaz; Andréa de Lima Ribeiro; Doreen Ebert; Salar Tavakkol; et al. (Fuel, 2025)

A terminology for downcycling - Christoph Helbig; Jonas Huether; Charlotte Joachimsthaler; Christian Lehmann; Simone Raatz; Andrea Thorenz; Martin Faulstich; Axel Tuma (Journal of Industrial Ecology, 2022)
The term downcycling is often used anecdotally to describe imperfections in recycling. However, it is rarely defined. Here, we identify six meanings of the term downcycling as used in scientific articles and reports. These encompass the material quality of reprocessed materials, target applications, product value, alloying element losses, material systems, and additional primary production. In a proposal for harmonized and more specific terminology, we define downcycling as the phenomenon of quality reduction of materials reprocessed from waste relative to their original quality. We further identify that the reduced quality can express itself thermodynamically, functionally, and economically, covering all perspectives on downcycling. Dilution, contamination, reduced demand for recycled materials, and design‐related issues can cause those downcycling effects. We anticipate that this more precise terminology can help quantify downcycling, keep materials in the loop longer, use materials more often and at higher quality, and therefore assist in reducing material‐related environmental impacts.